Kombinasi Relaksasi Otot Progresif dan Latihan Autogenik terhadap Kecemasan Keluarga Pasien yang Menjalani Perawatan Intensif: Penelitian Kuasi Eksperimen dengan Kelompok Terkontrol - Tahir, Rusna; Sartiya Rini, Dewi; Muhsinah, Sitti; Iqra S, Iqra S (Health Information : Jurnal Penelitian, 2022)
Patients undergoing intensive care can be perceived by their accompanying families as a condition of helplessness and life threatening, thus providing an anxious psychological response for the family. Progressive muscle training and autogenic relaxation as complementary therapies in previous studies can be used to help reduce anxiety. This study aims to determine the effect of a combination of progressive muscle training and autogenic relaxation on family anxiety, with a quasi-experimental design, pre-test and post-test with the control group. The instrument to measure family anxiety was using the STAI (State Trait Anxiety Inventory) questionnaire. The total sample was 60 respondents who were determined based on the non-probability sampling technique with the consecutive sampling method. There were 30 respondents in each intervention group and control group. The results showed that the combination of progressive muscle training and autogenic relaxation had an effect on decreasing family anxiety, and statistically the difference between the average anxiety in the intervention group and the control group was 14.5 with a P value of 0.000. Further research is needed to determine the standard of complementary therapy in combination with progressive muscle training and autogenic relaxation.